(untitled) (AYUSHDHARA, 2023)
Epididymal cysts are collection of fluid in a single sac (unilocular) or more than one (multilocular) as a result of dilatation of efferent epididymal tubules due to tubular obstruction with benign in nature and often bilateral in nature. It involves the development of fluid-filled sacs or cysts within the epididymis, a coiled tube located behind each testicle. An epididymal cyst, also known as a spermatocele that affects the male reproductive system. If it is not treated it may develop to an abscess and probably the destruction of the epididymis which can lead to infertility. In Ayurveda it can be under the heading Kaphaja Granthi. A 27-year-old male patient visited the outpatient department of Kayachikitsha with complaints of bilateral scrotal swelling with itching since six months. Patient was diagnosed on the basis of colour doppler of scrotum and it indicates bilateral epididymis head cyst with minimal fluid seen around left spermatic cord with herniation of omental fat on Valsalva. The patient was treated with classical management of Kapahaja Granthi described in texts, Vaman (medicated emesis), Virechana (therapeutic purgation) and followed by administered Arogyavardhini Vati 2 tablet each of 250mg twice a day in empty stomach, Kanchanara Guggulu two tablet each of 500mg twice a day after food with lukewarm water and Varunadi Kashaya 40ml once a day in morning empty stomach. After this treatment there was no scrotal swelling also the colour doppler study reveals normal colour doppler study with no significant abnormality noted. This case indicates the Ayurveda classical management given in texts can be helps to manage the condition like epidydimal cyst.